Fast coherent integration method for moving target detection with random PRI variation. Issue 1 (1st January 2020) - Zhu, Weiqiang; Liu, Zhiling; Xu, Huajian
Abstract : This Letter addresses the coherent integration problem for the moving target detection in a pulse repetition interval (PRI)‐staggered radar system. Due to the random sampling, the complex coupling effects between range and azimuth will severely degrade the target parameter estimation and coherent integration performance. To deal with this issue, a fast coherent integration detection method with random azimuth sampling is proposed, where range migration is firstly compensated by applying the range‐frequency reversal transform. Then, the random phase fluctuation caused by the staggered PRI can be efficiently removed by applying the non‐uniform FFT technique. Finally, a moving target can be well focused. Simulated results are provided to validate the effectiveness of the proposed algorithm.